- #1
soandos
- 166
- 0
where is the flaw in the following:
it is possible to define a 3d vector using the form:
(x,y,z) = (x_1,y_1,z_1)+t(a,b,c)
this can then be parameterized to become
x = x_1 + a*t
y = y_1 + b*t
z = z_1 +c*t
so, for example, given the vector (x,y,z) = (1,2,3) + t(5,6,7)
one can parametrize it to become:
x = 1 + 5t
y = 2 + 6t
z = 3 + 7t
solving the first equation for t gives
t = (x-1)/5
plugging that into the other two equations gives:
y = 2 + 6/5 * (x-1)
z = 3 + 7/5 * (x-1)
solving the second one for x gives:
x = (5*z-8)/7
changing y = 2 + 6/5 * (x-1) to y = 2 + 6/5 * (2x-x-1)
and in the -x spot putting -(5*z-8)/7 yeilds:
y = 2 + 6/5 * (2x-(5*z-8)/7-1)
simplifying gets:
76 = 35 y + 30 z - 84 x
which is the equation of a plane.
this cannot possibly be right as i started out with a 2-d object (the vector)
where did i mess up?
(p.s. i tried to do all of this algebraically but it got too ugly for me)
thanks.
it is possible to define a 3d vector using the form:
(x,y,z) = (x_1,y_1,z_1)+t(a,b,c)
this can then be parameterized to become
x = x_1 + a*t
y = y_1 + b*t
z = z_1 +c*t
so, for example, given the vector (x,y,z) = (1,2,3) + t(5,6,7)
one can parametrize it to become:
x = 1 + 5t
y = 2 + 6t
z = 3 + 7t
solving the first equation for t gives
t = (x-1)/5
plugging that into the other two equations gives:
y = 2 + 6/5 * (x-1)
z = 3 + 7/5 * (x-1)
solving the second one for x gives:
x = (5*z-8)/7
changing y = 2 + 6/5 * (x-1) to y = 2 + 6/5 * (2x-x-1)
and in the -x spot putting -(5*z-8)/7 yeilds:
y = 2 + 6/5 * (2x-(5*z-8)/7-1)
simplifying gets:
76 = 35 y + 30 z - 84 x
which is the equation of a plane.
this cannot possibly be right as i started out with a 2-d object (the vector)
where did i mess up?
(p.s. i tried to do all of this algebraically but it got too ugly for me)
thanks.